Endothelial cell adhesion to soluble vascular endothelial growth factor receptor‐1 triggers a cell dynamic and angiogenic phenotype. Issue 2 (30th October 2013) - Orecchia, Angela; Mettouchi, Amel; Uva, Paolo; Simon, Glenn C.; Arcelli, Diego; Avitabile, Simona; Ragone, Gianluca; Meneguzzi, Guerrino; Pfenninger, Karl H.; Zambruno, Giovanna; Failla, Cristina Maria
Abstract : The aim of this study was to identify the molecular signals produced in human endothelial cells (ECs) by the interaction of α5β31 integrin with soluble vascular endothelial growth factor receptor‐1 (sVEGFR‐1) present in the extracellular matrix. We generated a gene expression profile of ECs adhering to sVEGFR‐1 or to fibronectin, the classic extracellular matrix ligand for α5β1 integrin or in a nonadhering condition. Several biological pathways were differently modulated, 3 protein kinase C substrates [adducin, myristoylated alanine‐rich protein kinase C substrate (MARCKS), and radixin] were differently expressed and phosphorylated when cells adhering to sVEGFR‐1 were compared with those adhering to fibronectin. Rac1 activation and Gα13 protein involvement through the interaction with radixin were also detected after attachment to sVEGFR‐1, and these responses depended on active VEGFR‐2 signaling. On sVEGFR‐1, ECs exhibited a motile phenotype that was consistent with the abundant presence of MARCKS, a stabilizer of dynamic adhesions. Moreover, ECs silenced for radixin expression no longer responded to the proangiogenic VEGFR‐1‐derived peptide 12. We propose that the presence of sVEGFR‐1 in the EC microenvironment directs α5β1 integrin signaling to generate a dynamic, motile phenotype. Our findings also provide new insights into the mechanism of action of proangiogenic peptide 12, relevant to a therapeutic perspective.—Orecchia, A., Mettouchi, A., Uva, P., Simon, G.C., Areclli, D., Avitabile, S., Ragone, G., Meneguzzi, G., Pfenninger, K.H., Zambruno, G., Failla, C.M. Endothelial cell adhesion to soluble vascular endothelial growth factor receptor‐1 triggers a cell dynamic and angiogenic phenotype. FASEB J. 28, 692–704 (2014). www.fasebj.org